Growth Pattern of Different Body Dimensions in Female Kacang Goats - Galuh Fitria Yolanda; Ratna Kumala Dewi; Wardoyo (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2022)
The purpose of this study was to determine the growth patterns of female Kacang goats Growth Pattern of Different Body Dimensions in Female Kacang Goats. We measured 23 female goats for variables including body weight, chest circumference, shoulder height, and body length. The results showed that body weight followed the sigmoid curve pattern (S) with a regression equation y = 0.0005x3-0.0837x2 + 3.0707x + 0.119 with a coefficient of determination of 88.99%, while body size for chest circumference, body length, and shoulder height follows a polynomial pattern with regression equations y = -0.0627x2 + 3.1156x +40.333, y = -0.033x2 + 1.6941x + 43.125, and y = -0.0418x2 + 2.1168x + 39.089, respectively and the coefficient of determination was 85.26%, 82.46%, and 68.53%, respectively. The research conclude that the growth of body dimensions in livestock has fluctuated. The increase of body dimensions in female-goat goats peaked at the age of 21-30 months, then started to decline during 31-40 months. It is correlated with the fact that age greatly affects the dimensions of the animal body. The highest coefficient determination value was observed in body weight, namely 88.89%.